Conditional deletion of Abca3 in alveolar type II cells alters surfactant homeostasis in newborn and adult mice - Besnard, Valérie (American Physiological Society, 2010)
ATP-binding cassette A3 (ABCA3) is a lipid transport protein required for synthesis and storage of pulmonary surfactant in type II cells in the alveoli. Abca3 was conditionally deleted in respiratory epithelial cells (Abca3(Δ/Δ)) in vivo. The majority of mice in which Abca3 was deleted in alveolar type II cells died shortly after birth from respiratory distress related to surfactant deficiency. Approximately 30% of the Abca3(Δ/Δ) mice survived after birth. Surviving Abca3(Δ/Δ) mice developed emphysema in the absence of significant pulmonary inflammation. Staining of lung tissue and mRNA isolated from alveolar type II cells demonstrated that ∼50% of alveolar type II cells lacked ABCA3. Phospholipid content and composition were altered in lung tissue, lamellar bodies, and bronchoalveolar lavage fluid from adult Abca3(Δ/Δ) mice. In adult Abca3(Δ/Δ) mice, cells lacking ABCA3 had decreased expression of mRNAs associated with lipid synthesis and transport. FOXA2 and CCAAT enhancer-binding protein-α, transcription factors known to regulate genes regulating lung lipid metabolism, were markedly decreased in cells lacking ABCA3. Deletion of Abca3 disrupted surfactant lipid synthesis in a cell-autonomous manner. Compensatory surfactant synthesis was initiated in ABCA3-sufficient type II cells, indicating that surfactant homeostasis is a highly regulated process that includes sensing and coregulation among alveolar type II cells.